CCL17 exerts a neuroimmune modulatory function and is expressed in hippocampal neurons. Issue 10 (12th September 2018) - Fülle, Lorenz; Offermann, Nina; Hansen, Jan Niklas; Breithausen, Björn; Erazo, Anna Belen; Schanz, Oliver; Radau, Luca; Gondorf, Fabian; Knöpper, Konrad; Alferink, Judith; Abdullah, Zeinab; Neumann, Harald; et al.
Abstract: Chemokines are important signaling molecules in the immune and nervous system. Using a fluorescence reporter mouse model, we demonstrate that the chemokine CCL17, a ligand of the chemokine receptor CCR4, is produced in the murine brain, particularly in a subset of hippocampal CA1 neurons. We found that basal expression of Ccl17 in hippocampal neurons was strongly enhanced by peripheral challenge with lipopolysaccharide (LPS). LPS‐mediated induction of Ccl17 in the hippocampus was dependent on local tumor necrosis factor (TNF) signaling, whereas upregulation of Ccl22 required granulocyte‐macrophage colony‐stimulating factor (GM‐CSF). CCL17 deficiency resulted in a diminished microglia density under homeostatic and inflammatory conditions. Further, microglia from naïve Ccl17 ‐deficient mice possessed a reduced cellular volume and a more polarized process tree as assessed by computer‐assisted imaging analysis. Regarding the overall branching, cell surface area, and total tree length, the morphology of microglia from naïve Ccl17 ‐deficient mice resembled that of microglia from wild‐type mice after LPS stimulation. In line, electrophysiological recordings indicated that CCL17 downmodulates basal synaptic transmission at CA3–CA1 Schaffer collaterals in acute slices from naïve but not LPS‐treated animals. Taken together, our data identify CCL17 as a homeostatic and inducible neuromodulatory chemokine affecting the presence and morphology of microglia and synaptic transmission in the hippocampus. Main Points: CCL17 is constitutively expressed in pyramidal CA1 neurons and is further induced under inflammatory conditions. CCL17‐deficiency causes alterations in microglia morphology and basal synaptic transmission at CA3‐CA1 Schaffer collaterals.